2009
DOI: 10.1007/978-3-642-02737-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Subshifts, Languages and Logic

Abstract: We study the Monadic Second Order (MSO) Hierarchy over infinite pictures, that is tilings. We give a characterization of existential MSO in terms of tilings and projections of tilings. Conversely, we characterise logic fragments corresponding to various classes of infinite pictures (subshifts of finite type, sofic subshifts).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Aubrun and Kari have shown that the Baumslag Solitar groups have undecidable domino problem [1]. Ballier and Stein [2], building on results from several authors [19][20] [16] [15], observe that every virtually free group has decidable domino problem, and conjecture that these are the only such groups.…”
Section: Known Resultsmentioning
confidence: 99%
“…Aubrun and Kari have shown that the Baumslag Solitar groups have undecidable domino problem [1]. Ballier and Stein [2], building on results from several authors [19][20] [16] [15], observe that every virtually free group has decidable domino problem, and conjecture that these are the only such groups.…”
Section: Known Resultsmentioning
confidence: 99%
“…In this paper, we will prove how various classes of formula correspond to well known classes of subshifts. Some of the results of this paper were already presented in [26].…”
Section: Introductionmentioning
confidence: 79%
“…We continue the line of research of [5,6], and define subshifts by monadic secondorder (MSO) formulas. We now introduce the terminology used in these articles, and then expand upon it.…”
Section: Logical Formulasmentioning
confidence: 99%
“…In this article, we follow the approach of [5,6] and define two-dimensional subshifts by monadic second-order (MSO) logical formulas. We show that certain hierarchies obtained by counting quantifier alternations are finite, solving an open problem posed in [6].…”
Section: Introductionmentioning
confidence: 99%